Alloreactivity of Allogeneic Mesenchymal Stem/Stromal Cells and Other Cellular Therapies: A Concise Review. (9th March 2022) - Shah, Kiran; Shah, Nirali; Ghassemi, Fatameh; Ly, Carolyn; George, Teena; Lutz, Carla; Sumer, Huseyin
Abstract : Cellular therapies, deemed live medicine, have brought a wave of new generation biological therapies to treat previously untreatable diseases such as cancers and degenerative diseases like osteoarthritis. These cellular therapies have gained significant recognition in clinical research. The area has been further strengthened with the approval of Chimeric Antigen Receptor added on T cells (CAR-T) therapies by the regulatory authorities USA's Food and Drugs Administration (FDA), European Medical Agency (EMA), the Australian Therapeutic Goods Administration (TGA), and in many countries in 2017 to treat hematological cancers. Another milestone was achieved when allogeneic Mesenchymal Stem Cell- (MSC-) based therapy was approved by the EMA to treat Chrohn's disease in 2018. Allogeneic donor-derived MSC therapies in particular hold great promise and real hope because of their 'off-the shelf' availability and accessibility for patients in need of urgent treatment. So far, thousands of clinical trials have explored the safety and efficacy of both autologous and allogeneic cell therapies, deeming them safe, however with varying degrees of efficacy. In the current pandemic, clinical trials have begun in many parts of the world to treat severe cases of COVID with MSCs. However, the risk of tissue rejection and the development of undesirable effects due to alloreactivity of allogeneic cells are currently not adequately addressed. Therefore, this warrants careful investigation and detailed reporting of such events by clinical researchers. This review aims at discussing the current landscape of approved allogeneic MSCs along with a few other cellular therapies. We explore any possible reactivity reported to inform the readers of any safety concern and on the efficacy of such therapies.